HIV disease duration, but not active brain infection, predicts cortical amyloid beta deposition. (15th July 2021) - Morgello, Susan; Cortes, Etty P.; Gensler, Gary; Meloni, Gregory; Jacobs, Michelle M.; Murray, Jacinta; Borukov, Valeriy; Crary, John F.
Abstract : Objective: Abnormal deposition of the antimicrobial peptide amyloid beta (Aβ) is a characteristic of Alzheimer's disease. The objective of this study was to elucidate risk factors for brain Aβ in a cohort enriched for HIV and other neurotropic pathogens. Design: Cross-sectional cohort study. Methods: We examined autopsy brains of 257 donors with a mean age of 52.8 years; 62% were men; and 194 were HIV+ and 63 HIV−. Hyperphosphorylated tau (p-tau) and Aβ were identified in frontal and temporal regions by immunohistochemistry. APOE genotyping was performed. Clinical and neuropathological predictors for Aβ were identified in univariate analyses, and then tested in multivariate regressions. Results: Cortical Aβ was identified in 32% of the sample, and active brain infection in 27%. Increased odds of Aβ were seen with increasing age and having an APOE ε4 allele; for the overall sample, HIV+ status was protective and brain infection was not a predictor. Within the HIV+ population, predictors for Aβ were duration of HIV disease and APOE alleles, but not age. When HIV disease duration and other HIV parameters were introduced into models for the entire sample, HIV disease duration was equivalent to age as a predictor of Aβ. Conclusion: We hypothesize that dual aspects of immune suppression and stimulation in HIV, and beneficial survivor effects in older HIV+ individuals, account for HIV+ status decreasing, and HIV duration increasing, odds of Aβ. Importantly, with HIV, disease duration replaces age as an independent risk for Aβ, suggesting HIV-associated accelerated brain senescence.